2011
DOI: 10.1021/je200146j
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Speeds of Sound in l-Leucine/l-Isoleucine + Aqueous K2SO4/KNO3 Systems at (298.15 to 323.15) K

Abstract: Density (ρ) and speed of sound (u) values have been measured of l-leucine + 0.5 mol·L–1 aqueous K2SO4/KNO3 and l-isoleucine + 0.5 mol·L–1 aqueous K2SO4/KNO3 systems for several molal concentrations of l-leucine/l-isoleucine at different temperatures T = (298.15, 303.15, 308.15, 313.15, 318.15, and 323.15) K. Using the experimental values of ρ and u, the apparent molar volumes, partial molar volumes, transfer partial molar volumes, isentropic compressibilities, apparent molar isentropic compressibilities, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The denaturation of a protein in different aqueous solutions containing salts is an important behavior of biological molecules and has been the subject of extensive investigation. However, the complex configurational and conformational aspects of protein structure in aqueous solution, make it very difficult to directly interpret various biological processes with salts. In recent years, it is recognized that the physicochemical investigations of aqueous solutions containing amino acids or small peptides are of considerable importance and will be helpful in the fundamental understanding of denaturation and other complicated biological processes. Among these technologies, volumetric studies , can provide some unique information in terms of ligand-binding properties, as well as the folding/unfolding character and conformational stability of a globular protein. , …”
Section: Introductionmentioning
confidence: 99%
“…The denaturation of a protein in different aqueous solutions containing salts is an important behavior of biological molecules and has been the subject of extensive investigation. However, the complex configurational and conformational aspects of protein structure in aqueous solution, make it very difficult to directly interpret various biological processes with salts. In recent years, it is recognized that the physicochemical investigations of aqueous solutions containing amino acids or small peptides are of considerable importance and will be helpful in the fundamental understanding of denaturation and other complicated biological processes. Among these technologies, volumetric studies , can provide some unique information in terms of ligand-binding properties, as well as the folding/unfolding character and conformational stability of a globular protein. , …”
Section: Introductionmentioning
confidence: 99%
“…The decrease in φ v may be due to strong ion-ion interaction and vice-versa. The negative values of φ v indicate electrostrictive solvation of ions [16]. From the magnitude of φ k , it can be concluded that stronger molecular association is found in Lvaline than in other two amino acids.…”
Section: Resultsmentioning
confidence: 97%
“…Studies of the effect of concentration of salt and temperature on the thermodynamical properties of the aqueous amino acids solutions have been proven to be very useful in elucidating the various interactions that occur in these solutions. The volumetric and compressibility studies of amino acids in aqueous salt solution have been employed to understand the nature of interactions operative in solution [4][5][6]. It has been established that metal ions play crucial role in various biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study of interactions of saccharides and their derivatives with metal ions and H 2 PO 4 – /PO 4 3– ions in water is of major importance. Very few studies on the solution behavior of saccharides in the presence of monobasic salts, that is, NaH 2 PO 4 , NH 4 and H 2 PO 4 , and tribasic salts, that is, K 3 PO 4 , are available in the literature. Therefore, to elucidate the interactions among saccharides and phosphate salts, various physicochemical techniques such as densimetry, viscometry, calorimetry, and sound velocity measurements are being employed.…”
Section: Introductionmentioning
confidence: 99%